Colloidal Cerium Oxide Nanoparticles: Preparation and Corrosion Inhibition Performance on AA5005 Aluminum Alloy. Issue 2 (27th January 2018) - Ecco, L. G.; Rossi, S.; Deflorian, F.; Fedel, M.
Abstract : This study investigated the potential of ceria nanoparticles to reduce the corrosion rates of AA5005 immersed in chloride-rich media at neutral pH. The colloidal ceria nanoparticle dispersion was prepared via precipitation of cerium (III) ions in presence of citric acid. Transmission electron microscopy and dynamic light scattering confirmed the fine structure of ceria; crystallites lower than 10 nm with a hydrodynamic diameter average size of about 30 nm were obtained. Potentiodynamic polarization and electrochemical impedance spectroscopy measurements were conducted on bare AA5005 panels exposed to 0.1 M NaCl with different quantities of ceria nanoparticles. Polarization curves revealed a significant reduction of cathodic current densities for AA5005 immersed in ceria containing electrolytes when compared to the background solution, i.e. a shift toward lower current densities of about one order of magnitude for those containing 5.0 and 7.5% of ceria. Impedance spectra with higher moduli at low frequencies were obtained for AA5005 immersed in ceria containing electrolytes. In general, while in contact to the ceria-containing electrolytes the rates of localized corrosion attacks at the surface of AA5005 were found to decrease and, the outputs from the electrochemical tests suggested an inhibition effect of the colloidal ceria nanoparticles prepared in this work.